2016
DOI: 10.3390/w8010027
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Benthic Macroinvertebrate Assemblages in Relation to Environmental Variables in Korean Nationwide Streams

Abstract: Conserving and enhancing freshwater biodiversity are global issues to ensure ecosystem integrity and sustainability. To meet this, it is critical to understand how the biological assemblages are determined by environmental gradients in different spatial scales. Nevertheless, information on their large-scale environmental relationships remains scarce in Korea. We aimed to understand nationwide spatial distribution patterns of benthic macroinvertebrates and important environmental factors affecting their distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 63 publications
6
53
0
Order By: Relevance
“…This is reflected in evidence supporting our hypotheses regarding the relationships between land use and the connectance of our co-occurrence networks (H2), and the mean strength of their co-occurrences (H3). Evidence supporting our hypothesis regarding a negative correlation between network size and land use (H1) reflects a well-established link between environmental stress and both the loss of biodiversity and measures of biotic integrity (Freeman & Schorr, 2004;Garie & McIntosh, 1986;Jun et al, 2016Jun et al, , 2011. We find the importance of network size, along with network connectance and co-occurrence strength, reinforces prior observations on the importance of both regional and local measures of environmental quality in BMI communities (Stoll et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…This is reflected in evidence supporting our hypotheses regarding the relationships between land use and the connectance of our co-occurrence networks (H2), and the mean strength of their co-occurrences (H3). Evidence supporting our hypothesis regarding a negative correlation between network size and land use (H1) reflects a well-established link between environmental stress and both the loss of biodiversity and measures of biotic integrity (Freeman & Schorr, 2004;Garie & McIntosh, 1986;Jun et al, 2016Jun et al, , 2011. We find the importance of network size, along with network connectance and co-occurrence strength, reinforces prior observations on the importance of both regional and local measures of environmental quality in BMI communities (Stoll et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that Ephemeroptera dominated the invertebrate composition mainly by Baetidae and though in limited abundance, Heptageniidae was recorded at the sites. This pattern was found in some Asian streams [3]; Leuctridae and Perlodidae were recorded for the presence of Plecoptera while Rhyacophilidae, Hydropsychidae and Limnephilidae composed the Trichoptera. The differences between sites were linked to differences in abundance rather than taxonomically different families.…”
Section: Benthic Macroinvertebrate Communitiessupporting
confidence: 55%
“…Variables associated with altitude reveal local environmental factors which determine the structure and distribution of benthic macroinvertebrate communities [3]. A limited composition of benthic macroinvertebrates accounted for a combination of ultimate (altitude, catchment area and slope) and proximate (BOD, phosphate-P, conductivity and discharge) factors.…”
Section: Physicochemical Variables and The Community Of Benthic Macromentioning
confidence: 99%
See 1 more Smart Citation
“…Jun et al [14] studied nationwide distribution patterns of benthic macroinvertebrates and important environmental factors affecting their spatial distribution using the data obtained from the NAEMP. They classified 720 sampling sites into five clusters according to the pollution levels from fast-flowing, less-polluted streams with low electrical conductivity to moderately or severely polluted streams with high electrical conductivity and low water velocity.…”
Section: Contributionsmentioning
confidence: 99%